Skin cancer in organ transplant recipients: dynamics in the incidence and clinical predictors for the first and subsequent post‐transplant non‐melanoma skin cancer. (3rd April 2019) - Hartmann, J.; Schüler, S.; Enk, A.H.; Lonsdorf, A.S.
Abstract: Background: Risk factors for primary non‐melanoma skin cancer (NMSC) in organ transplant recipients (OTR) have been well described. Data for subsequent NMSC and dynamics in their occurrence in OTR are limited. Objective: To study long‐term risks of primary and subsequent NMSC and associated risk factors in OTR. Methods: A retrospective single‐centre cohort study analysing medical records from a dermato‐oncological specialty clinic. Results: Of 464 OTR 110 (23.7%) developed at least one, 73 (15.7%) two and 51 (11%) three NMSC during a median follow‐up of 9.6 years. Cumulative incidences at 5, 10 and 15 years were 14.7%, 23.5% and 34.5% for the first and 75.8%, 86.5% and 93.3% for the second. Median time‐to‐diagnosis declined from 22 years (95% CI 19–25) to 2 years (1–3) and about 1 year (0–2) for the first, second and third NMSC. Risk for subsequent NMSC only partially related to risk factors for the primary NMSC. Histologic type of the first NMSC predicted subtype and time‐to‐diagnosis of the subsequent NMSC. Conclusions: A first post‐transplant NMSC, particularly a SCC, confers a high risk for subsequent NMSC arising with accelerated dynamics. Risk‐adapted dermato‐oncologic surveillance is advisable for all OTR.